Analisis Pengaruh Pelatihan, Motivasi Kerja, Kompensasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada Hotel Grand Setia Kawan Solo - Kusuma, Jeanita Ika; , Sri Murwanti, SE., MM (2017)
This study aimed to determine the effect of training, motivation, compensation and work discipline on employee performance. The sample in this study are employees working at the Hotel Grand Setia Kawan Solo amounted to 85 employees. The sampling technique in this research is to use the formula slovin. The method used in this study is testing instrument, the classical assumption test (normality test, multicollinearity, heteroskedasitas test), multiple linear regression, hypothesis testing (t test and F) and the coefficient of determination (R ^ 2). Results from this study is testing the hypothesis states that the training and motivation have significant influence on employee performance is evidenced by the t test, while compensation and working discipline does not have significant influence is evidenced by the t test. In the F test showed that together the variables of training, motivation, compensation and discipline significant influence on employee performance. Keywords: training, motivation, compensation, work discipline and performance employees.